(untitled) (KONFERENSIYA, 2025)
This article examines the ethical responsibilities of translators and the importance of professional behavior when working with multilingual communication. It highlights such key ethical principles as confidentiality, accuracy, neutrality, and respect for cultural differences. The study emphasizes that adhering to professional standards helps translators build trust, prevent misunderstandings, and ensure the integrity of communication between parties